TEACHER’S INITIATION IN ENGLISH CLASSROOM INTERACTION BASED ON SINCLAIR AND COULTHARD MODEL - Nurmiati Sitompul; Siti Aisah Ginting; Isli Iriani Indiah Pane (Universitas Negeri Medan, 2018)
This study was about teacher’s initiation in English classroom interaction based on Sinclair and Coulthard Model. The aimed of this study were (a) to find out the types of teacher’s initiations used in English classroom interaction based on Sinclair and Coulthard Model, (b) to find out the dominant type of teacher’s initiation used in English classroom Interaction based on Sinclair and Coulthard Model, and (c) to find out the reason why the teacher used the dominant type of initiation during the teaching and learning process. This research used qualitative research. To answer the problems of the study, the data were collected in three ways by observing, recording and interviewing. The data were analyzed based on Sinclair and Coulthard theory (1975). The result of this study were the following, (a) There were nine types of teacher’s initiations found during the teaching and learning process, namely, teacher elicit, teacher inform, teacher direct, listing, re-initiation (i), re- initiation (ii), check, repeat, and boundary. (b) the dominant type of teacher’s initiation used in English classroom interaction was teacher elicit, which was 40%. (c) the reasons why the teacher used the dominant type of initiation during the teaching and learning process was categorized based on the variables that were affected on teaching and learning process (Gage,2004), they were: the teacher believed that by initiating elicit, it could create an effective classroom interaction, the teacher believed that by initiating elicit, it could push the students on process of flashback, the teacher believed that by initiating elicit, the students would be encouraged to become more confident and braver to participate actively during the teaching and learning process.Key words: Teacher’s Initiation, Classroom Interaction, Sinclair and Coulthard.